Complement Activation by CpG in a Human Whole Blood Loop System: Mechanisms and Immunomodulatory Effects - Mangsbo, Sara M. (2009)
Phosphorothioate oligodeoxynucleotides can activate complement, and experimental murine studies have revealed differential effects upon simultaneous TLR stimulation and complement activation compared with either event alone. We set out to investigate the immune stimulatory effects of CpG 2006 in fresh non-anticoagulated human blood with or without presence of active complement. We also sought to elucidate the mechanism behind complement activation upon stimulation with phosphorothioate CpG 2006. In a human blood loop system, both backbone and sequence-specific effects by CpG were counteracted by selective inhibition of C3. Furthermore, DNA backbone-mediated CD40 and CD83 expression on monocytes and sequence-specific IL-6 and TNF production were reduced by complement inhibition. CpG-induced complement activation occurred via either the classical or the alternative pathway and deposits of both IgM and properdin, two activators of complement, were detected on CpG after incubation with EDTA plasma. Quartz crystal microbalance with dissipation monitoring demonstrated alternative pathway convertase build-up onto CpG as a likely pathway to initiate and sustain complement activation. Specific inhibition of C3 suppressed CpG 2006 uptake into monocytes indicating that C3 fragments are involved in CpG internalization. The interplay between complement and TLR9 signaling demonstrated herein warrants further investigation.